Insights Into the Regulation of Offspring Growth by Maternally Derived Ghrelin - Sato, Takahiro; Ida, Takanori; Shiimura, Yuki; Matsui, Kazuma; Oishi, Kanae; Kojima, Masayasu (Frontiers in Endocrinology, 2022)
The regulation of fetal development by bioactive substances such as hormones and neuropeptides derived from the gestational mother is considered to be essential for the development of the fetus. On the other hand, it has been suggested that changes in the physiological state of the pregnant mother due to various factors may alter the secretion of these bioactive substances and induce metabolic changes in the offspring, such as obesity, overeating, and inflammation, thereby affecting postnatal growth and health. However, our knowledge of how gestational maternal bioactive substances modulate offspring physiology remains fragmented and lacks a systematic understanding. In this paper, we focus on ghrelin, which regulates growth and energy metabolism, to advance our understanding of the mechanisms by which maternally derived ghrelin regulates the growth and health of the offspring. Understanding the regulation of offspring growth by maternally-derived ghrelin is expected to clarify the fetal onset of metabolic abnormalities and lead to a better understanding of lifelong health in the next generation of offspring.